Evaluasi Kehilangan Gaya (Force Decay) Elastomeric Chain pada Perendaman Minuman Teh Kemasan (Evaluation of Force Decay Elastomeric Chain on The Immersion of Tea Packaging) - Medina Nanda Utami; Hafiedz Maulana; Rudy Joelijanto (Pustaka Kesehatan, 2016)
Background : Force decay elastomeric chain can be caused by evironmental factors in the oral cavity suchas temperature,pH, saliva andalso drinks have been consumed. Tea beverage has an acidic pH which is suspected influencing force decay in elastomeric chain, so that tooth movement can not be optimal during orthodontic treatment. Objective : To analyze the loss of high force on elastomeric chain due to immersion of tea beverage. Method : Samples consisted of two groups, they are control group using artificial saliva and the treatment group using artificial saliva then added to the tea beverage. The trearment group were immersed in the solutions three times a day for 5 minutes every 24 hours. Force (grF) was measured using Autograph Machine, initially (0 hours), 0,5 hours, 1,5 hours, 3,5 hours, 7,5 hours, 24 hours and 48 hours. Result and Conclusion : The result showed no significant different between the groups of control and treatment groups. The conclusion from this research shown that elastomeric chain immersed in tea beverages packagingand saliva increased forcedecaygreater than the elastomeric chain that just immersedin saliva,but the difference was not significant. Keywords : elastomeric chain, force decay,tea beverage.